A Pocket Guide to Analyzing Films - Robert Spadoni (University of California Press, 2014)
A Pocket Guide to Analyzing Films is founded on the belief that most any film can be better understood and appreciated when it is viewed as a system in which the parts relate to each other and together make up the whole. Thinking about a film in this way is sometimes called â€œclose readingâ€ and sometimes â€œtextual analysis.â€ We will call it formal analysis. Because it focuses exclusively on describing the methods of formal analysis, and on making a case for their usefulness regardless of oneâ€™s specific interest in the cinema, this book leaves out a lot of things. It concentrates on those aspects of the film-viewing experience that donâ€™t change, or have changed the least, over time. Thereâ€™s nothing, or close to it, on silent versus sound cinema, IMAX, Technicolor, YouTube, and 3-D. And thereâ€™s a minimum on how techniques are executed, on behindthe- scenes production realities like optical printers, performance capture suits, Final Cut Pro, and stunt doubles. The focus, instead, is on the results of these efforts, what happens on the screen, the functions and effects of these techniques both individually and, more important, when they work together. There is little mention of the turn to digital cinema in recent years, because the thing that weâ€™ll be calling â€œfilm formâ€ has not been remade by this change. The methods, terminology, and target of the kind of analysis described in this book have not experienced the upheavals currently sweeping the worldâ€™s cinema institutions, technologies, and economies. Thereâ€™s no overview of the movie business today or even a snapshot of movie history. And this isnâ€™t a how-to guide for aspiring filmmakers. That said, filmmakers who want to learn more about how films shape the viewing experience will find here a concise road map to the tools and principles that govern this dynamic and richly complex process.